The thrill of estrangement' : ethnicity and theatrical reality in Les Amertumes, Combat de Negre et de Chiens and Quai Ouest by Bernard-Marie Koltes - Fancy, David Hamish (Trinity College (Dublin, Ireland). Department of Drama, 2003)
This thesis consists of an analysis of ethnicity and modes of theatrical reality in three plays by French dramatist Bernard-Marie Koltes, made possible by a convergence of critical strategies from postcolonialism, phenomenology and semiotics. I trace a variety of progressions related to questions of the representation of ethnicity and theatrical reality from Koltes' earliest play, Les Amertumes, through to the first two of his plays staged by French director Patrice Chéreau, Combat de negre et de chiens and Quai ouest. The analysis of Les Amertumes consists of an exploration of how certain important tendencies related to essentialist protrayals of identity in the later two plays are very present in Koltes' earliest creative project and vision. Most significantly, Koltes' early work as a theatre practitioner, and his expectations about how his audiences should receive the theatrical event, are explored with a view to understanding their bearing on his later playwrighting. I bring to bear a variety of theoretical models on the text and evidence from the productions, including discussions of semiotics, phenomenology, and logocentrism in the history of acting theory. Special emphasis is placed on Les Amertumes' central character, Alexis, who shares many traits with the central characters of the later plays.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin